Pulmonary vein capture is a predictor for long-term success of stand-alone pulmonary vein isolation with cryoballoon ablation in patients with persistent atrial fibrillation - Babak, Alexey; Kauffman, Christine Bienvenue; Lynady, Cynthia; McClellan, Reginald; Venkatachalam, Kalpathi; Kusumoto, Fred (Frontiers in Cardiovascular Medicine, 2024)
Background The mechanisms of AF development and progression are still not completely understood. Despite the relative efficacy of ablation, the risk of AF recurrence is substantial, particularly in patients with persistent AF (perAF). At present we do not have any reliable intra-procedural electrophysiologic predictors of long-term success of AF ablation other than pulmonary vein isolation. We evaluated selected intraprocedural pulmonary vein characteristics that may be helpful in future guidance of persistent AF ablation. Methods 390 consecutive procedures using cryoballoon for initial AF ablation were divided by clinical presentation (paroxysmal or persistent AF), and by pulmonary vein (PV) response to pacing after completion of ablation (discrete electrogram elicited with pacing—“PV capture” or not—“Control”). Patients were followed (median 20 months) for recurrent atrial arrhythmias as the primary end point of the study. Results PV capture was identified in 20.3% and 17.1% and patients with paroxysmal and persistent AF respectively (ns). In patients with persistent AF presence of PV capture was associated with significantly better outcomes compared to patients without PV capture (p < 0.001). In the group “persistent AF and PV capture”, an initial strategy of PV isolation and reisolation of the PVs (without additional lesions) for patients with recurrent atrial arrhythmias resulted in 20/23 (87%) patients in sinus rhythm off antiarrhythmic medications at study completion. In patients with paroxysmal AF, PV capture was not associated with outcome benefits. Speciﬁc electrophysiologic characteristics of PV (PV capture cycle length: PVCCL) did not have an impact on AF recurrence, although 25% shortening of PVCCL was observed after 60 s periods of pacing at short cycle lengths. No background demographic patient characteristic differences were identiﬁed between patients with vs. without PV capture. Conclusion The presence of PV capture was associated with better outcomes in patients with persistent AF. PV capture may identify those patients with persistent AF in whom cryoballoon PV isolation alone is sufficient as an initial ablation procedure and as the primary ablation strategy for recurrent AF.